Early Intranasal Vasopressin Administration Impairs Partner Preference in Adult Male Prairie Voles (Microtus ochrogaster) - Simmons, Trenton C.; Balland, Jessica F.; Dhauna, Janeet; Yang, Sang Yun; Traina, Jason L.; Vazquez, Jessica; Bales, Karen L. (Frontiers in Endocrinology, 2017)
Research supports a modulatory role for arginine vasopressin (AVP) in the expression of socially motivated behaviors in mammals. The acute effects of AVP administration are demonstrably prosocial across species, providing the justification for an ever-increasing measure of clinical interest over the last decade. Combining these results with noninvasive intranasal delivery results in an attractive system for offering intranasal AVP (IN-AVP) as a therapeutic for the social impairments of children with autism spectrum disorder. But, very little is known about the long-term effects of IN-AVP during early development. In this experiment, we explored whether a single week of early juvenile administration of IN-AVP (low = 0.05 IU/kg, medium = 0.5 IU/kg, high = 5.0 IU/kg) could impact behavior across life in prairie voles. We found increases in fecal boli production during open field and novel object recognition testing for the medium-dose in both males and females. Medium-dose females also had significantly more play bouts than control when exposed to novel conspecifics during the juvenile period. Following sexual maturity, the medium and high-doses of IN-AVP blocked partner preference formation in males, while no such impairment was found for any of the experimental groups in females. Finally, the high-dose selectively increased adult male aggression with novel conspecifics, but only after extended cohabitation with a mate. Our findings confirm that a single week of early IN-AVP treatment can have organizational effects on behavior across life in prairie voles. Specifically, the impairments in pair-bonding behavior experienced by male prairie voles should raise caution when the pro-social effects of acute IN-AVP demonstrated in other studies are extrapolated to long-term treatment.